2016
DOI: 10.1021/jacs.6b03547
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electronic Structure, and Reactivity Studies of a 4-Coordinate Square Planar Germanium(IV) Cation

Abstract: A tetra-coordinate, square planar germanium(IV) cation [(TPFC)Ge](+) (TPFC = tris(pentafluorophenyl)corrole) was synthesized quantitatively by the reaction of (TPFC)Ge-H with [Ph3C](+)[B(C6F5)4](¯). The highly reactive [(TPFC)Ge](+) cation reacted with benzene to form phenyl complex (TPFC)Ge-C6H5 through an electrophilic pathway. The key intermediate, a σ-type germylium-benzene adduct, [(TPFC)Ge(η(1)-C6H6)](+), was isolated and characterized by single-crystal X-ray diffraction. Deprotonation of [(TPFC)Ge(η(1)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…At about 98°, the angle between Ge1‐S1‐Ge2 lies in the middle, and the most obtuse angle is the one between S1‐Ge2‐C1 (about 117°). An additional thf molecule is coordinated to the central germanium atom, thus leading to a Ge−O bond length of 208.0 pm, which is comparable to the Ge−O bond length of 206.8 pm within [(TPFC)Ge(thf) 2 ] + (TPFC=tris(pentafluorophenyl)corrole) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At about 98°, the angle between Ge1‐S1‐Ge2 lies in the middle, and the most obtuse angle is the one between S1‐Ge2‐C1 (about 117°). An additional thf molecule is coordinated to the central germanium atom, thus leading to a Ge−O bond length of 208.0 pm, which is comparable to the Ge−O bond length of 206.8 pm within [(TPFC)Ge(thf) 2 ] + (TPFC=tris(pentafluorophenyl)corrole) …”
Section: Resultsmentioning
confidence: 99%
“…An additional thf molecule is coordinated to the central germanium atom, thus leadingt oaGeÀOb ond length of 208.0 pm,w hich is comparable to the GeÀOb ond length of 206.8 pm within [(TPFC)Ge(thf) 2 ] + (TPFC = tris(pentafluorophenyl)corrole). [28] Scheme4.Synthesis of germylene (thf)Ge[S-GeCl 2 -Tsi] 2 (4)a long two different reaction pathways. 3), Ge1ÀO1 208.0(2), Ge2ÀCl1 217.64(9); S2-Ge1-S1 86.02(3),G e1-S1-Ge2 98.03(3),S 1-Ge2-C1 117.51(9),C l1-Ge2-Cl299.78 (4).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these fitting results, the calculated coordination number of Pt atoms in Pt-uni-MOS was 4 with an average Pt-S bond length of 2.32 Å. EXAFS spectroscopy thus revealed that each atomic Pt site was coordinated with four sulfur atoms to form a Pt-S4 configuration. Such a tetracoordinate macrocyclic M-X4 model is thermodynamically stable in the field of metalloproteins or organometallics [49,50]. From the Wavelet transform (WT) spectrum (Fig.…”
Section: X-ray Absorption Analysis Of Pt-uni-mosmentioning
confidence: 99%
“…Previously, we reported the synthesis of corrole Ge( iii ) radicals, 9 Ge( iv ) cation complexes, 10 and a corrole Sn( ii ) complex. 11 However, the preparation of high valent corrole tin complexes with well-exposed tin centers, i.e.…”
Section: Introductionmentioning
confidence: 99%